When it comes to container port efficiency, are all developing regions equal?. (April 2016) - Suárez-Alemán, Ancor; Morales Sarriera, Javier; Serebrisky, Tomás; Trujillo, Lourdes
Highlights: We develop a port productivity and efficiency analysis of all developing regions. Productivity growth rates are explained by pure efficiency changes. We find an upward trend for port efficiency in developing regions. Private sector increases the level of port efficiency in developing regions. Country-level policies may not be the best choice for improving port efficiency. Abstract: In this paper we carry out a container port performance analysis of the developing world between 2000 and 2010, using both parametric and nonparametric approaches. From a unique dataset – our sample covers 70 developing countries, 203 ports, and 1750 data points–, we examine the evolution and drivers of productivity and efficiency changes across developing regions. We show that productivity growth rates between 2000 and 2010 vary significantly and that this heterogeneity is explained by pure efficiency changes rather than scale efficiency of technological changes. Therefore, we carry out a detailed efficiency analysis to determine the drivers of port efficiency. Time series results show an upward trend for port efficiency in developing regions, as it increased from 51 percent in 2000 to 61 percent in 2010. Our analysis indicates that private sector participation, the reduction of corruption in the public sector, improvements in liner connectivity and the existence of multimodal links increase the level of port efficiency in developing regions.